1999
DOI: 10.1055/s-1999-13642
|View full text |Cite
|
Sign up to set email alerts
|

Premedication, Preparation, and Surveillance

Abstract: During the last two years, the well-known positive role of benzodiazepines (midazolam and diazepam) in conscious sedation, both in adults and pediatric patients, has been confirmed by several studies. However, problems concerning the role of sedation and analgesia in nonoperative endoscopy are still a matter of debate. Particular attention has focused on attempts to identify the "ideal candidate" for conscious sedation, and on the importance of providing patients with information before the procedure, which sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 31 publications
0
31
0
1
Order By: Relevance
“…Although the use of sedation during upper gastrointestinal endoscopy is prevalent (4,5), there is much debate about the administration of sedatives. While some investigators propose that sedation-related complications may develop (6,7), many have reported that conscious sedation increases comfort during upper gastrointestinal endoscopy and reduces cardiac stress (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Although the use of sedation during upper gastrointestinal endoscopy is prevalent (4,5), there is much debate about the administration of sedatives. While some investigators propose that sedation-related complications may develop (6,7), many have reported that conscious sedation increases comfort during upper gastrointestinal endoscopy and reduces cardiac stress (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…It should be borne in mind that national and even regional differences may affect evaluation of pre-medication results. 16 The results obtained in this study show that significant decreases in midazolam doses may be obtained with psychiatric intervention in endoscopy-intolerant patients. The next step would be to investigate the routine clinical application of psychosomatic treatment, which has been found to be useful for endoscopy patients in our study.…”
Section: Psychiatric Intervention In Intolerances In Endoscopic Procementioning
confidence: 57%
“…The morbidity and mortality associated with cardiopulmonary complications persist as a significant issue of concern during gastrointestinal endoscopy practice, and guidelines for sedation and analgesia call for continuous monitoring of the patient's hemodynamic and ventilatory status and consciousness. Direct observation is facilitated by electronic devices (pulse oximetry) (21). Monitoring of oxygen saturation (SpO2) and heart rate and systolic blood pressure was performed in all patients during the colonoscopy in this study.…”
Section: Discussionmentioning
confidence: 99%